Curcumin modulated gut microbiota and alleviated renal fibrosis in 5/6 nephrectomy-induced chronic kidney disease rats. - Cheng Li; Xulong Chen; Jingchun Yao; Weiwei Zha; Meiren Li; Jiangwen Shen; Hongli Jiang; PuXun Tian (PLoS ONE)
Increasing evidence suggests that dysbiosis of gut microbiota exacerbates chronic kidney disease (CKD) progression. Curcumin (CUR) has been reported to alleviate renal fibrosis in animal models of CKD. However, the relationship between CUR and gut microbiome in CKD remains unclear. This study aims to investigate the potential anti-renal fibrosis effects of CUR from the gut microbiota perspective. A 5/6 nephrectomy (5/6Nx) rat model was used to explore the therapeutic effect of CUR on renal fibrosis. Tight junction protein expression levels were measured to assess intestinal barrier function. 16S rRNA sequencing was employed to evaluate changes in gut microbiota composition, and metabolomics was utilized to detect alterations in plasma metabolites. The administration of CUR significantly ameliorated renal fibrosis and inhibited inflammation in 5/6Nx rats. Additionally, CUR markedly improved the expression of tight junction proteins and local colon inflammation. CUR also positively reconstructed gut microbiota, significantly increasing the abundance of beneficial bacteria, such as Lachnospiraceae_NK4A136_group, Eubacterium_siraeum_group, and Muribaculaceae was significantly increased. Metabolomics revealed that CUR reduced uremic retention solutes and elevated Vitamin D and short-chain fatty acids (SCFAs). Spearman correlation analysis indicated that gut genera enriched by CUR were positively correlated with Vitamin D and SCFA and negatively correlated with chronic renal injury biomarkers. Mechanistically, we found inhibition of the LPS/TLR4/NF-κB and TGF-β1/Smads pathway in CUR-treated rats. Our study indicates that CUR has the potential to modulate gut microbiota composition, and that this modulation may contribute to the anti-fibrosis effects of CUR.